Assessment and management of cytokine release syndrome and neurotoxicity following CD19 CAR-T cell therapy. (2nd June 2020) - Chou, Cassie K.; Turtle, Cameron J.
ABSTRACT: Introduction : The success of CD19 chimeric antigen receptor (CAR)-T cell therapy for treatment of CD19 positive malignancies has led to the FDA approval of two CD19 CAR-T cell products, tisagenlecleucel and axicabtagene ciloleucel, and ongoing clinical trials of new products. Cytokine release syndrome (CRS) and neurotoxicity are common toxicities associated with CD19 CAR-T cell therapies. Areas covered : This review will discuss CRS and neurotoxicity associated with CD19 CAR-T cell therapies, including clinical presentation, risk factors, pathophysiology, and therapeutic or prophylactic interventions. Expert opinion : In conjunction with improved understanding of the pathophysiology of CRS and neurotoxicity, we expect that the recent development of consensus guidelines for the evaluation of these toxicities will enhance management of patients undergoing CD19 CAR-T cell therapies.